Hungarian Monitoring, 22 May 1989 . [Magyar rádiófigyelő], 1989. május 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Correspondence, reports, conversations on situation in Beijing - Pravda article on situation in the Baltic - Honecker-Jaruzelski meeting - Harsh article in Bratislava Pravda on cessation of Nagymaros dam construction - Spiegel article on Hungarian-Czechoslovak relations Domestic Affairs: - Mátyás Szűrös: political and legal rehabilitation of Imre Nagy and colleagues is necessary - Foreign minister Gyula Horn: Imre Nagy and colleagues were victims of a political show trial - Not true that opposition roundtable would break off talks with Hungarian Socialist Workers' Party (MSZMP), although the MSZMP awaits opposition's response to Central Committee's proposal - Reforms can help form Party unity, says Mihály Jassó - Nagymaros construction: Austrian Greens' arguments against, claims for damages submitted - Judit Csehák's lecture on ideas to reform social insurance - Conversation about SZETA's activities Economy: - According to head of government, Hungary must hold back socialist exports because of neighboring countries' behavior - Hungarian-Cypriot economic relations - How is it possible that land in Hungary has neither value nor price? Külpolitika: - Tudósítások jelentések, beszélgetés a pekingi helyzetről - Pravda cikk a Baltikum helyzetéről - A Honecker-Jaruzelski találkozó - A pozsonyi Pravda keményhangú cikke a nagymarosi építkezés leállításáról - Der Spiegel-cikk a magyar-csehszlovák viszályról Belpolitika: - Szűrös Mátyás szerint szükséges Nagy Imre és társai politikai és jogi rehabilitációja - Nagy Imre és társai politikai indíttatású koncepciós perek áldozatai voltak, jelentette ki Horn Gyula külügyminiszter - Nem igaz, hogy az ellenzéki kerekasztal megszakította volna a tárgyalásokat az MSZMP-vel, viszont az MSZMP az ellenzék válaszát várja a KB indítványára - A reformkörök segíthetik a pártegység kialakulását, jelentette ki Jassó Mihály - A nagymarosi építkezés: osztrák zöldek ellenérvei; kárigények beterjesztése - Csehák Judit előadása a tb megreformálásával kapcsolatos elképzelésekről - Beszélgetés a SZETA tevékenységéről Gazdaság: - A magyar kormányfő szerint Magyarországnak vissza kell fognia szocialista exportját a környező országok tartozásai miatt - Magyar-ciprusi gazdasági kapcsolatok - Hogyan lehetséges az,hogy Magyarországon a földnek se értéke, se ára nincsen?